2022
DOI: 10.1186/s12985-022-01942-8
|View full text |Cite
|
Sign up to set email alerts
|

Profiling genome-wide recombination in Epstein Barr virus reveals type-specific patterns and associations with endemic-Burkitt lymphoma

Abstract: Background Endemic Burkitt lymphoma (eBL) is potentiated through the interplay of Epstein Barr virus (EBV) and holoendemic Plasmodium falciparum malaria. To better understand EBV’s biology and role in eBL, we characterized genome-wide recombination sites and patterns as a source of genetic diversity in EBV genomes in our well-defined population of eBL cases and controls from Western Kenya. Methods EBV genomes representing 54 eBL cases and 32 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
1
0
2
Order By: Relevance
“…For example, Panea et al and Agwati et al reported that EBV type 1 tumors have a higher mutational load compared to EBV type 2. 8,54 It is also known that Type 1 more effectively immortalizes B-cells 55 and is more prevalent in endemic BL patients compared to healthy controls in Africa. 56 Based on our findings, however, it seems that these differences do not translate to differential patient survival time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Panea et al and Agwati et al reported that EBV type 1 tumors have a higher mutational load compared to EBV type 2. 8,54 It is also known that Type 1 more effectively immortalizes B-cells 55 and is more prevalent in endemic BL patients compared to healthy controls in Africa. 56 Based on our findings, however, it seems that these differences do not translate to differential patient survival time.…”
Section: Discussionmentioning
confidence: 99%
“…Нуклеотидные последовательности анализировали с помощью открытого программного обеспечения «MEGA X» («Mega Software») 1 .…”
Section: материалы и методыunclassified
“…ВЭБ характеризуется генетическим разнообразием, которое обусловлено длительной эволюцией, включающей ряд аспектов. Показано, что рекомбинация играет определяющую роль в формировании разнообразия ВЭБ и структуры его генома [1]. Зафиксированы признаки диверсифицирующего отбора на уровне генов латентной фазы, функция которых заключается в переходе активной инфекции ВЭБ к длительной персистенции [2].…”
Section: Introductionunclassified